Review on machining of additively manufactured nickel and titanium alloys - KAYNAK, YUSUF (ELSEVIER, 2021)
The machining of nickel and titanium-based superalloy components is very expensive and involves unusually high lead times compared with other engineering metals such as steels and aluminum. This has led to the development of most suitable additive manufacturing (AM) processes to fabricate these difficult-to-machine metals into near-net shape parts, thereby reducing the lead time and material waste, and significantly increasing productivity. Nonetheless, finish machining is still required on the AMed metal components to meet the dimensional and surface requirements of the application. Several research studies have investigated the machinability of AMed nickel and titanium alloy workpieces and have compared the results with the machining responses of wrought counterparts, which is detailed in this review. The categorization of the literature is based on the machining operations including turning, milling, drilling, and non-conventional machining, and the observations are discussed in accordance with various input parameters such as workpiece characteristics (hardness, microstructures) and anisotropy in mechanical properties due to build orientations during the AM process. Moreover, the influence of these parameters on cutting forces and temperatures, chip formation, and tool wear is analyzed and reported. From this review, it is found that the machinability of AMed nickel and titanium workpieces is quite different to the machining responses of their wrought counterparts. Further thorough experimentation is required to develop optimized machining parameters for AMed metal parts, while an exploration of different cutting tool geometries, coolant, and lubrication strategies for enhanced tool performance for machining AMed workpieces is essential. Finally, this study reviews the state of contemporary research, and offers suggestions for future research. (c) 2021 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Machining; Additive manufacturing; Nickel alloy; Titanium alloys; Tool wear analysis; Surface integrity analysis; BEAM MELTED TI6AL4V; SURFACE INTEGRITY; TI-6AL-4V COMPONENTS; TOOL WEAR; MICROSTRUCTURE; MACHINABILITY; DRY; PARAMETERS; BEHAVIOR; FATIGUE